Prostate Volume Index Stratified Prostate Cancer Risk in Patients Elected to a First Random Biopsy Set. Issue 4 (July 2017) - Porcaro, Antonio B.; Corsi, Paolo; de Luyk, Nicolò; Sebben, Marco; Tafuri, Alessandro; Bizzotto, Leonardo; Cacciamani, Giovanni; De Marchi, Davide; Processali, Tania; Mattevi, Daniele; Novella, Giovanni; Cerruto, Maria A.; et al.
Objective: To investigate prostate volume index (PVI), defined as the ratio of volume of the transitional zone on that of the peripheral zone, as a factor stratifying prostate cancer (PCA) risk in patients elected to a first random biopsy set. Methods: The study evaluated 596 patients who were elected to a first random biopsy set because of suspected PCA in a period between September 2010 and September 2015. Prostate volume index was dichotomized to PVI ≤1 vs PVI >1. The multivariate logistic regression model investigated clinical factors with dichotomized PVI associating with PCA. Results: The detection rate of PCA was 49%. The dichotomized PVI >1 stratified PCA risk (odds ratio [OR] 0.455; p<0.0001) beyond age (OR 1.062; p<0.0001), PSA (OR 1.167; p<0.0001), PV (OR 0.957; p<0.0001), and abnormal digital rectal examination (OR 2.094; p<0.0001). The goodness of fit statistics assessed model efficacy. Conclusions: A large cohort of patients elected to a first random biopsy set had PCA risk stratified by dichotomized PVI beyond other clinical independent factors. Confirmatory studies are required.